Gestão de riscos associados a cultivos agroenergéticos por meio da modelagem espaço-temporal de parâmetros agrometeorológicos e do monitoramento da vegetação com imagens de sensoriamento remoto: estudo de caso em lavouras de milho safrinha - Meira, Maurício Braga (2013)
Agriculture is the economic activity mostly depended on climate conditions. The climate events affect not only the plant metabolic, directly related to crop production, as well the most diverse activities in the field. According to Petr (1990) e Fageria (1992), mentioned by Hoogenboom (2000), around 80% of the worldwide crop production variability is due to the climate conditions variability during the crop cycle, especially for rainfed agriculture as the producers cannot make any control over the natural phenomena. In addition to influence the crop growing, crop development and crop production, the climate also affect the plant relation with microorganisms, insects, fungus and bacteria, helping or not to allow for plagues or diseases, which demands the appropriate controlling mechanisms. Most of the crop practices as soil preparation, seeding, fertilizing, irrigation, and specific input applications depending on particular weather and soil humidity specifications to be executed efficiently (PEREIRA et al., 2002). Due to the great importance of the climate to the crop production, the use of meterological and climate informations are fundamental to turn agriculture into a sustainable activity. (SIVAKUMAR et al. 2000). Under this context, the agrometeorology, interdisciplinary science that studies the influence of weather and climate on the food, fibers and energy production assumes strategic position to comprehend and solve problems facing by agriculture (MAVI E TUPPER, 2004). Governments’ usually supports the risk management from producers focusing on unpredictable and non-avoided, possible rare, with huge consequences (catastrophic losses) if producers could not manage these risks alone as there are a limited political options to be considered as an internal or international levels when the issue is about feed the citizens. The most recent worries about the worldwide population growing, degradation of natural resources and about sustainability in agriculture has been demanding for bigger efforts on the development of better strategies and land use practices towards a better knowledge about the relations among crop and climate. Therefore, the development of tools that may help the planning procedures and could support the decision making process to result in less environment impacts and on improve the agricul- ture resilience has been one of the main purpose of government institutions and nongovernment organizations linked to agriculture, environment and natural resources. Besides the sophisticate technicians applied to accurate estimate future prices, the unstable perspectives related to the crop commodities results into the hypothesis that in normal conditions, the climate related uncertainty, macroeconomic circumstances, political interventions, energy costs among other relevant factors suggests the crop commodities prices will remain unpredictable ahead. Even considering hedging strategies will remain predominant in regarding the financial risk mitigation derived price volatility, for the majority of the food companies, crop insurance and producers who depend on harvesting to earn the profits out of agriculture production, as well as for most of the agribusiness related organizations, mitigate market price risks together with agrometeorological risks makes sense. The use of a decision support tool based on geographic information system is the best way to take advantage of all knowledge available to monitor the crop and bioenergy production. Spatial filters applied to the analyze of overall crop status aligned with information products updated on time to check the crop yield at a farm level allows truly to monitor the risks associates to the agro meteorological conditions and the crop management practices. The technological convergence among the information and decision support systems through cloud based servers allows nowadays automatizing most of the analysis derivate from the available information to make it knowledge flow until the end users. The network of companies formed to produce spatial data, ether by employing remote sensing satellites or meteorological stations are prepared to guarantee a continuous flux of information ready to be consumed by the end users of this knowledge. The results of this work and the conclusions of this investigation confirm the hypothesis when information is communicated smartly, on time to be used on effective decision making allows a better mitigation of the risks associated to crop production thus could generate value to shareholders that may have assets linked to the agribusiness. The biggest challenge of this Master Science work is to show for agribusiness players that whenever facilitating to producers a simple way to them manage its own rural activity based on best practices related to agrometeorological monitoring, enabling mechanisms to assist for a better rural management and supporting the access to information, not only providing ad doc support and agronomic aids, it certainly improve the risk management competences related to agro and forest activities.